In Search of Overcoming the Anthropological Crisis - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
An anthropological crisis emerges in contemporary society which stems from profound changes of values and meaning of life resulting from the intensive development of technological environment and the very nature of human nature and leading to the disappearance of social-cultural conditions typical for the traditional society. On the bases of analysis of modern and traditional types of overcoming the anthropological crisis, the author suggests following a new principle of rationality that integrates the truth and the ethical, instrumental rationality and value rationality, which immanently involves reflection over values. It is assumed that the worldview of real humanism which has human life, human dignity, and nonviolence as its axiological basis, is important for overcoming the anthropological crisis. This axiological trinity will save humanity from the deadly enticement of the impulsive all-permissiveness.